Histoire des crues du Roubion (Drôme, France) depuis 1501 AD, une approche hydrologique des fluctuations climatiques sur cinq siècles - Philippe Thoumas (Physio-Géo)
An archival research concerning the hydrological information was led on the catchment area of the Roubion, Mediterranean tributary of the left bank of the Rhône. From the collected data then from their interpretation, we show that a more important hydrological activity both in term of frequency and intensity occurred during the Little Ice Age but continued until the XXth century. From the beginning of 1960s, we entered for a period of quiet hydrologic novel for 500 years. Others lessons learned, summer floods which were very wide-spread tend to disappear. These conclusions are in line with studies led by other researchers on several Mediterranean streams, including a sedimentological study on the downstream part of the basin. Despite profound changes in its catchment area, the climatic origin seems to explain the hydrological fluctuations observed.